2020
DOI: 10.1051/0004-6361/202038077
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the ageing effect to the observed asymmetry of interplanetary magnetic clouds

Abstract: Context. Large magnetic structures are launched away from the Sun during solar eruptions. They are observed as (interplanetary) coronal mass ejections (ICMEs or CMEs) with coronal and heliospheric imagers. A fraction of them are observed in situ as magnetic clouds (MCs). Fitting these structures properly with a model requires a better understanding of their evolution. Aims. In situ measurements are made locally when the spacecraft t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 61 publications
8
24
0
Order By: Relevance
“…From EUHFORIA simulations, we report values of ζ CME ranging between 1.09 and 0.63 at the different heliocentric distances considered (Subsection 4.5). Such numbers are comparable with typical observational values at 1 au, which suggests the asymmetries in the CME magnetic field profile are primarily due to actual cross-section asymmetries, although ageing may still provide a significant contribution leading to a mix of the two effects (Démoulin et al 2020). For the particular CME considered, and based on our simulations, we consider ageing may be most relevant for heliocentric distances closer than 0.5 au, where ζ CME was higher than 0.8, while at distances larger than 0.5 au the lower expansion rates (ζ CME < 0.8) suggest cross-sectional asymmetries as the dominant source of magnetic asymmetry.…”
Section: Evolution Of the Magnetic Field Profilesupporting
confidence: 84%
See 2 more Smart Citations
“…From EUHFORIA simulations, we report values of ζ CME ranging between 1.09 and 0.63 at the different heliocentric distances considered (Subsection 4.5). Such numbers are comparable with typical observational values at 1 au, which suggests the asymmetries in the CME magnetic field profile are primarily due to actual cross-section asymmetries, although ageing may still provide a significant contribution leading to a mix of the two effects (Démoulin et al 2020). For the particular CME considered, and based on our simulations, we consider ageing may be most relevant for heliocentric distances closer than 0.5 au, where ζ CME was higher than 0.8, while at distances larger than 0.5 au the lower expansion rates (ζ CME < 0.8) suggest cross-sectional asymmetries as the dominant source of magnetic asymmetry.…”
Section: Evolution Of the Magnetic Field Profilesupporting
confidence: 84%
“…Previous studies agree in considering the latter to be typically dominant at 1 au. However, the ageing effect has been found to be the main source of magnetic asymmetry for a significant minority of magnetic ejectas at 1 au, making the consideration and correction for its effects worthwhile, in particular, in the case of large events (Démoulin et al 2020). Furthermore, we note that the effect of ageing at different heliocentric distances than 1 au, particularly those closer to the Sun, cannot be discarded a priori when interpreting the results obtained from EUHFORIA simulations.…”
Section: Evolution Of the Magnetic Field Profilementioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, we find that the velocity changes by less than 20% across the ME. In particular, we do not observe the consequence of such an expansion on the magnetic profile for ICMEs without a sheath, which implies the same on its extension with the magnetic flux conservation (see Démoulin et al 2020, for an analysis of expansion). Moreover, the evolution of these geometrical parameters are counteracted by a weaker magnetic field (due to magnetic flux conservation), so a less effective screening with time.…”
Section: Recovery In the Icme Wakementioning
confidence: 64%
“…Inside the MEs of both types of sheaths, the magnetic field fluctuations stabilise to lower levels since MEs are low-beta structures.The abrupt transitions in the magnetic field strength, proton density, and dynamic pressure (see first, fourth, and fifth panel of Figure2) at the front of the MEs are also more pronounced for propagation sheaths. For both types of sheaths, the magnetic field strengths at the leading edges are higher compared to the rear, leading to asymmetric magnetic field profiles inside the MEs (seeDémoulin et al 2008) Démoulin et al (2020). suggested that these asymmetric magnetic field profiles can possibly occur due to a stronger compression on one side of the ME.…”
mentioning
confidence: 99%